2017
DOI: 10.31989/ffhd.v7i6.337
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and phenolic contents of Ajwa date and their effect on lipo-protein profile

Abstract: Background: Date pits although being rich in phenolic and antioxidant content are neglected part and treated as waste product. Ethanobotanical records indicates potential of ajwa dates pits and flesh having phenolics, antioxidants and some other nutrients.Objective: The study was planned to extract the phenolic contents and antioxidant activity of ajwa date flesh and pits in comparison to local date varieties, in three different solvents with three different concentrations and to observe their effect on high l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 6 publications
3
16
0
4
Order By: Relevance
“…This correlation analysis suggests that high phenol content of soybean seed is followed with high antioxidant activity when measured with the DPPH method. The present study is supporting the research results reported by several researchers who found a positive correlation between total phenol and antioxidant activities in soybean and other plant species [12,14,[16][17][18][19][20][21][22] . Therefore, it could be suggested that total phenol is a good initial indicator of antioxidant activities.…”
Section: Correlation Between Phenolic Content and Antioxidant Activitysupporting
confidence: 93%
“…This correlation analysis suggests that high phenol content of soybean seed is followed with high antioxidant activity when measured with the DPPH method. The present study is supporting the research results reported by several researchers who found a positive correlation between total phenol and antioxidant activities in soybean and other plant species [12,14,[16][17][18][19][20][21][22] . Therefore, it could be suggested that total phenol is a good initial indicator of antioxidant activities.…”
Section: Correlation Between Phenolic Content and Antioxidant Activitysupporting
confidence: 93%
“…Extract of grapes rich in flavonoids is an important nutraceutical ingredient of food. For effective utilization of these phytochemicals it is necessary to understand the chemistry of flavonoid constituents in different food matrices and to improve the method of extraction, characterization, authentication and quantification of these phytochemicals and assess their biological activity against different diseases (Cushnie and Lamb 2005, Ahmad et al 2015, Khalid et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that oral administration of 250 and 500 mg/kg body weight of lyophilized Ajwa extract to rats treated with isoproterenol to induce myocardial infraction, improved cardiac oxidative stress and inflammation markers, and serum lipoprotein profile (Al-Yahya et al, 2016). Despite the great ethnopharmacological uses and significant nutritional potential of Ajwa dates, studies on the antihypercholesterolemic properties of Ajwa dates polyphenol extracts are scarce (Al-Yahya et al, 2016;Khalid, Ahmad, & Kaleem, 2017) and more are still required.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that oral administration of 250 and 500 mg/kg body weight of lyophilized Ajwa extract to rats treated with isoproterenol to induce myocardial infraction, improved cardiac oxidative stress and inflammation markers, and serum lipoprotein profile (Al‐Yahya et al, ). Despite the great ethnopharmacological uses and significant nutritional potential of Ajwa dates, studies on the antihypercholesterolemic properties of Ajwa dates polyphenol extracts are scarce (Al‐Yahya et al, ; Khalid, Ahmad, & Kaleem, ) and more are still required. The effectiveness of the phenolic compounds obtained from dates as antioxidants in in vitro and in vivo studies depends on many factors, such as the date variety, extraction method, and solvent, as well as the part of the date fruit used (Abdul‐Hamid, Abas, Ismail, Shaari, & Lajis, ; Khalid, Ahmad, et al, ).…”
Section: Introductionmentioning
confidence: 99%